Perturbed Angular Correlation Studies in the Ferromagnetic Rare Earths - McMath, Thompson Andrew (My University, 1967)
A low temperature apparatus has been constructed for the purpose of studying perturbed angular correlations in the ferromagnetic rare earth elements. The rotation of the 966.4 keV gamma vibrational state in 160Dy was measured to be (1.61 ± 0.33) milliradians.
Keywords: perturbed, angular, correlation, ferromagnetic rare earths, temperature, vibrational, gamma